Effect of Oil Viscosity on Rheology of Coal–Oil Mixtures. Issue 5 (3rd September 2017) - Ganeshan, G.; Panda, D.
ABSTRACT: Studies on rheological behavior of coal–oil mixtures up to 50% concentration by weight of coal have been carried out using Indian coals of varying ash content. Both high-viscous and low-viscous oils have been used with a temperature variation from 30°C to 70°C. Viscosity was measured using a Haake RV 100 rotational viscometer with an MV II sensor system. For a coal–high-viscous-oil system, a generalized correlation correlating relative viscosity of slurry to coal concentration and density of solid is proposed. For a coal–low-viscous-oil system, an empirical equation correlating suspension viscosity with a non-dimensional parameter C v / C vmax with temperature variation has been proposed.